Antioxidant, antilipidemic and antidiabetic effects of ficusin with their effects on GLUT4 translocation and PPARγ expression in type 2 diabetic rats. (25th August 2016) - Irudayaraj, Santiagu Stephen; Stalin, Antony; Sunil, Christudas; Duraipandiyan, Veeramuthu; Al-Dhabi, Naif Abdullah; Ignacimuthu, Savarimuthu
Abstract: In this study, the antioxidant, antilipidemic and antidiabetic effects of ficusin isolated from Ficus carica leaves and their effects on GLUT4 translocation and PPARγ expression were evaluated in HFD-STZ induced type 2 diabetic rats. Ficusin (20 and 40 mg/kg b. wt.) lowered the levels of fasting blood glucose, plasma insulin and body weight gain, in HFD-STZ induced diabetic rats. Ficusin also significantly lowered the serum antioxidant enzymes (SOD, CAT and GPx) and lipids (TC, TG and FFA) levels to near normal. Ficusin significantly enhanced the PPARγ expression and improved the translocation and activation of GLUT4 in the adipose tissue. Molecular docking analysis exhibited promising interactions of GLUT4 and PPARγ into their active sites. This study suggests that ficusin improved the insulin sensitivity on adipose tissue and it can be used for the treatment of obesity related type 2 diabetes mellitus. Highlights: Ficusin was isolated from Ficus carica leaves. Ficusin restored the body weight, blood glucose, plasma insulin and lipid levels to normal. Ficusin increased the PPARγ expression in adipose tissue. Ficusin enhanced GLUT4 translocation and activation. Ficusin docked with PPARγ and GLUT4.